The limits of participatory democracy: Social movements and the displacement of disagreement in South America - Ana Cecilia Dinerstein; Juan Pablo Ferrero (University of Bath, Centre for Development Studies (CDS), 2012)
Recent experiences of social movements in South America and the expansion of non-institutional forms of collective action have given rise to new conceptual frameworks such as participatory democracy, which aim to capture the impact of new forms of participation and collective action on democracy in the region. As a means of exploring the possibilities of deepening democracy, such frameworks have taken as their focal point the institutionalisation of 'alternative' forms and processes of participation. However, the focus on institutionalisation has usually bypassed the more radical dimensions of the discourses and practices of the movements-the 'disagreement' at their heart. By way of illustrative cases of two contemporary movements from Argentina (Piqueteros) and Brazil (Movement of Rural Landless Workers) we focus on two questions: What is the contribution of social movements to the process of democratisation? To what extent is such contribution being captured by new scholarly work on participatory and deliberative democracy? We analyse the political struggle within, against and beyond democratic 'borders' led by social movements in three historical moments. By distinguishing the dimensions of 'real policies' and 'imagined politics' we suggest that new conceptualisations such as 'participatory democracy' are unable to recognise the alternative democratic realities that emerge out of disagreement and play a regulatory role in transforming disagreement into dissent. Hope is then lost in translation. We suggest that Radical Democratic Theory can offer a better work of translation, as it is able to grasp the vital dimension of movements' collective action that resists integration into the hegemonic cannon, thus reflecting the movements' own reflection of their emancipatory collective action.
Keywords: 330; Democracy; disagreement; Rancière; social movements; South America; theory